Hematocrit and Hemoglobin Levels in Pregnant Women with Preeclampsia in Palembang City - Ardiya Garini; Agita Jeni Iswari; Asrori Asrori (Journal of Noncommunicable Diseases Prevention and Control, 2023)
Preeclampsia is a collection of symptoms that arise in pregnant, maternity, and postpartum women in the form of hypertension, edoema, and proteinuria that appear in the 20th week of pregnancy until the end of the first week after delivery. Several parameters of hematological examination in pregnant women are hematocrit and hemoglobin levels, which are suspected to be different between normal pregnant women and pregnant women who have preeclampsia. This study aims to determine the levels of hematocrit and hemoglobin in pregnant women with preeclampsia at RSIA Rika Amelia Palembang in 2021. This research is descriptive in nature, with a total sample size of 105 patients. The results of the study showed that the average hematocrit level in preeclamptic pregnant women was 37% and the hemoglobin level was 12 g/dl. Statistical tests showed no difference in hematocrit levels based on the mother's age (p-value = 0.678) or gestational age (p-value = 0.226). Meanwhile, for the hemoglobin level parameter, statistical tests showed no difference in hemoglobin levels based on the mother's age (p-value = 0.386) or gestational age (p-value = 0.104). It can be concluded that there is no difference in hematocrit and hemoglobin levels in preeclamptic pregnant women based on age and gestational age.